2019
DOI: 10.1002/jsfa.10038
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced microbial respiration due to carbon sequestration in pruning litter incorporated soil reduced the net carbon dioxide flux from atmosphere to tea ecosystem

Abstract: BACKGROUND: Tea (Camellia sinensis L.) bushes are periodically (at 3-4 year intervals) pruned (cut from top) to maintain vegetative growth stage and constant height. Plant residues (prunings litter) generated after pruning are generally left in the field as a potential source of organic matter in soil. Organic carbon (C) sequestration due to pruning litter incorporation is expected to increase microbial activity in soil. Being an evergreen plant, tea bushes assimilate atmospheric carbon dioxide (CO 2 ) through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…These authors concluded that increases in soil moisture were associated to significant increases in CO 2 emissions in irrigated orchards. On the contrary, the lack of differences in emissions between DIV and MC may indicate that current soil management in MC with frequent tillage and incorporation of pruning residues (Table S1) also contributes to high soil GHG emissions, as reported in literature (García-Orenes et al, 2010;Morell et al, 2010;Pramanik and Phukan, 2020). The lack of correlations between CO 2 emission and soil properties such as texture, pH, EC, TOC, Nt, nitrates and ammonium may suggest that climatic conditions and management are controlling CO 2 emissions by soil microbial activation through the presence of alley crops, tillage or pruning residues additions rather than inherent soil characteristics.…”
Section: Discussionmentioning
confidence: 83%
“…These authors concluded that increases in soil moisture were associated to significant increases in CO 2 emissions in irrigated orchards. On the contrary, the lack of differences in emissions between DIV and MC may indicate that current soil management in MC with frequent tillage and incorporation of pruning residues (Table S1) also contributes to high soil GHG emissions, as reported in literature (García-Orenes et al, 2010;Morell et al, 2010;Pramanik and Phukan, 2020). The lack of correlations between CO 2 emission and soil properties such as texture, pH, EC, TOC, Nt, nitrates and ammonium may suggest that climatic conditions and management are controlling CO 2 emissions by soil microbial activation through the presence of alley crops, tillage or pruning residues additions rather than inherent soil characteristics.…”
Section: Discussionmentioning
confidence: 83%